Identifying mathematical models in managing Islamic investment products using Musyarakah concept / Maheran Mohd Jaffar … [et al.] - Mohd Jaffar, Maheran; Samson, Abd Aziz; Ismail, Rashidah; Abdul Maad, Hamdan (Research Management Institute (RMI), 2011)
The Islamic banking has emerged as a significant and popular banking system in Malaysia. At present, the Islamic banking is able to offer competitive alternatives to conventional products and services, In Malaysia, murabahah and bai bithaman ajil concepts are widely used in most of the products under Islamic banking. Unfortunately foreign investors especially from Middle East are inclined toward products which are based on musyarakah concept. Musyarakah contract is a joint venture between two or more parties and the profit is shared according to the agreed profit sharing ratio. None of the Islamic banks in Malaysia uses these concepts in more than 10% of their financial portfolio. This research has found that the common variables used in managing Islamic investment products offered by Islamic banks are the same as conventional banks except for the profit sharing rate offered by Islamic banks. The proposed musyarakah model is suitable in packaging Islamic investment products. Beside the proposed model, there are other musyarakah models that may be used in managing the investment between two parties. Nevetheless the proposed model is far better than the other models in internalizing the spirit of fairness and justice for all involved parties.